A Markov Model for Driver Turn Prediction - Krumm, John (Society of Automotive Engineers (SAE) 2008 World Congress, April 2008, 2008)
This paper describes an algorithm for making short-term route predictions for vehicle drivers. It uses a simple Markov model to make probabilistic predictions by looking at a driver’s just-driven path. The model is trained from the driver’s long term trip history from GPS data. We envision applications including driver warnings, anticipatory information delivery, and various automatic vehicle behaviors. The algorithm is based on discrete road segments, whose average length is 237.5 meters. In one instantiation, the algorithm can predict the next road segment with 90% accuracy. We explore variations of the algorithm and find one that is both simple and accurate. Video | Award.
Lloyd L. Withrow Distinguished Speaker Award